Value Creation by Ad-Funded Platforms - Gregor Langus; Vilen Lipatov (Center for Economic Studies and ifo Institute (CESifo), 2022)
We identify features of interactions on online platforms that make an ad-funded business model attractive for the platform, but also for consumers. We then show that ad-funded platforms heavily rely on data for their ability to create value for their users. Formally, we show that data restrictions may trigger a switch away from ad-funded to fee-funded model, resulting in a loss of consumer welfare. We also argue that restricting the effort to increase data quality weakens competition to the detriment of consumers.
Keywords: K21; L22; L40; M37; 330; ad-funded business model; data aggregation restrictions; targeted advertising; platform competition; merchant competition; transaction costs